Desmoglein-2 was a novel cancer-associated fibroblasts-related biomarker for oral squamous cell carcinoma - Jin Liu; Zhonghao Sun; Shihui Cao; Hao Dai; Ze Zhang; Jingtao Luo; Xudong Wang (BMC Oral Health)
Abstract Background Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer with alarmingly high morbidity. The cancer-associated fibroblasts (CAFs) play a pivotal role in tumor development, while their specific mechanisms in OSCC remains largely unclear. Our object is to explore a CAFs-related biomarker in OSCC. Methods Single-cell RNA sequencing (ScRNA-seq) analysis was used to pinpoint CAF clusters in OSCC samples. Differentially expressed genes and Cox regression analyses were used to identify candidate genes, and their functions were evaluated using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses. The prognostic performance of the identified biomarker was evaluated using receiver operating characteristic analysis. The qPCR and western blot were used to assess gene expression. The hub gene related immune characteristics were analyzed in independent cohorts, and gene expression differences between different immunotherapy response groups were investigated using Pearson correlation analysis. Results Desmoglein-2 (DSG2) was identified as a CAFs-related biomarker in OSCC exhibiting elevated expression compared to controls and being associated with poor prognosis. Enrichment analyses revealed that DSG2 was involved in signal transduction pathways like focal adhesion. The Area Under Curve values of DSG2 in predicting prognosis exceeded 0.6 in both training-set and validation-set. Furthermore, patients with low DSG2 expression were more likely to benefit from immunotherapy than those DSG2 highly expressed patients. Conclusion Our study identified DSG2 as a reliable CAFs-related prognostic biomarker in OSCC, providing a new reference for the mechanistic understanding and target therapy of this malignancy.